An effective, low-tech drop-off solution to facilitate the retrieval of data loggers in animal-tracking studies. Issue 1 (2nd January 2018) - Evens, Ruben; Beenaerts, Natalie; Ulenaers, Eddy; Witters, Nele; Artois, Tom
ABSTRACT: Studying the movement ecology of smaller birds generally implies the use of archival devices, which require retrieval in order to download tracking data. When recapturing fails, archival devices are usually lost and birds carry the devices for longer than necessary. We present a cheap, safe and simple method to detach archival devices from animals in a semi-controlled manner. We used Eco Balloon Ribbon, a water-soluble ribbon, to attach GPS loggers to European Nightjars Caprimulgus europaeus via tail mounts. The ribbon was used as a weak link that dissolved within two minutes after heavy rain. The deployment duration could be estimated by following weather forecasts and the GPS loggers retrieved using a GPS-enabled radio tag. During the course of one breeding season, we deployed 44 GPS loggers and successfully retrieved 39. Here, we share our experience with Eco Balloon Ribbon, describe how to deploy a GPS logger using the tail-mount technique and provide useful tips to increase the success of drop-offs. Our methods can improve the efficacy of tracking studies, reduce the impact on the study species, and facilitate licensing and obtaining fieldwork permissions. Furthermore, we believe that Eco Balloon Ribbon has great potential to serve also in the long-term tracking of wildlife, through its integration as a weak point in collars or harnesses.